Overcoming the shortcomings of U.S. plug-in electric vehicle policies. (October 2019) - Carley, Sanya; Zirogiannis, Nikolaos; Siddiki, Saba; Duncan, Denvil; Graham, John D.
Abstract: We evaluate plug-in electric vehicle (PEV) policies currently implemented across the U.S. and the potential for these policies to facilitate widespread PEV diffusion. We examine the relationship between overlapping regulatory and fiscal policies at the federal and state levels of government. We argue that the current suite of policies is not as effective as it could be, and potentially more expensive. Our analysis suggests the existence of a tradeoff between the goals of increasing the market penetration of PEVs and that of limiting greenhouse gas emissions from the light-duty vehicle fleet. The way federal and state policies interact puts those two goals at odds, at least in the short-term. Drawing from the policy and economics literatures, we summarize a series of recommendations and incentives that could deliver a more balanced approach to the achievement of those two policy goals. We conclude with some research suggestions. Highlights: We examine four main PEV deployment policies currently in place in the U.S. Policy objectives are to accelerate deployment of PEVs and reduce greenhouse gases. We identify the conflicting incentives those policies offer. We address the implications from the lack of their coordination. We propose ways to better integrate the policies.